Evaluation of ghrelin and leptin in chronic obstructive pulmonary disease - Uysal, Pelin; Uzun, Hafize (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2019)
OBJECTIVE: Recent studies suggest an important role for ghrelin and leptin in pathogenesis of inflammatory respiratory diseases. Therefore, the present study aimed to investigate ghrelin and leptin levels in the circulation that might be associated with the development of obstruction. METHODS: Stable chronic obstructive pulmonary disease (COPD) patients (n= 119) and matched healthy controls (n = 27) were recruited. The COPD patients were classified into four groups (A, B, C, and D) according to the Revised Global Initiative for Chronic Obstructive Lung Disease guidelines. RESULTS: Compared to controls, significantly decreased leptin and ghrelin levels were observed in all COPD patient groups. Plasma ghrelin concentration was higher in Group A (P < 0.001), Group B (P < 0.001), and Group C (P < 0.05) when compared with the Group D. Plasma leptin concentration was significantly decreased in Group D patients when compared with Group A (P < 0.001) and Group B (P< 0.001). Ghrelin levels were positively correlated with forced expiratory volume in 1 s (FEV1) (r= 0.822

P< 0.001), FEV1/forced vital capacity (FVC) (r= 0.431: P < 0.01), and leptin (r = 0.808

P < 0.001) in Group D. Leptin showed positive correlation with FEV1 (r = 0.856: P < 0.001) and FEV1/FVC (r = 0.376

P < 0.05) in Group D. FEV1 was positively correlated with ghrelin levels (r= 0.639

P< 0.001) and leptin levels (r= 0.602

P < 0.001) in Group C. CONCLUSION: The data of the present study showed that the serum ghrelin and leptin levels are lower in patients with COPD. Since ghrelin and leptin correlate with FEV1 in severe group of patients, they seem to be a potential biomarker candidate of prognosis in COPD. Decreased ghrelin and leptin levels might be associated with the development of obstruction.
Keywords: Chronic obstructive pulmonary disease; forced expiratory volume in 1 s; forced expiratory volume in 1 s/forced vital capacity; ghrelin; leptin